2022
DOI: 10.7759/cureus.29756
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Case of Aspergillus Infection of the Brain and Its Future Medical Implications

Abstract: Aspergillus is a fungal genus found worldwide, which causes infection most commonly in the respiratory system and in other systems, including the central nervous system. Fungal species, such as Aspergillus fumigatus or flavus, are more common in immunocompromised patient populations, such as those taking immunosuppressants post-transplantation, those on long-term corticosteroids, or those with immunodeficiencies such as AIDS. In this paper, we describe a rare case of aspergillosis that occurred due to a histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…This infection spreads brain and cause lesions in a parenchyma of the brain due to defective cellular immunity. The brain lesions were secondarily resulted in fungal blood spread that reaches the brain [25]. Contextually, study demonstrated the brain of a patient infected with A. flavus.…”
Section: Discussionmentioning
confidence: 99%
“…This infection spreads brain and cause lesions in a parenchyma of the brain due to defective cellular immunity. The brain lesions were secondarily resulted in fungal blood spread that reaches the brain [25]. Contextually, study demonstrated the brain of a patient infected with A. flavus.…”
Section: Discussionmentioning
confidence: 99%